Penerapan Hukum Surat Berharga Dalam Dunia Perbankan - Muhammad Sultan Rahmadhani; Nur Fatimatul Laili; Sumriyah Sumriyah (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Securities are financial instruments or assets that have a monetary value issued by authorities such as banks or other institutions. These securities are in the nature of an agreement, which has a strictly regulated legal basis. So no one person or institution can abuse the use of these securities. This study uses a qualitative research approach that is designed using a methodology designed to provide a rich and contextual description of the phenomenon from the focus of this research itself. This study aims to gain an in-depth perception of how the law applies to the use of securities in the banking world, which is packaged with a relevant qualitative research design.